COMPARISON BETWEEN PREFERENCE OF SWIFTLET HOUSING DESIGN AND CHARACTERISTICS BY RANCHERS IN SABAH AND SARAWAK - Wan Hayati Husna Wan Nor Asma; Nur Hardy Abu Daud; Nurarina Aslah Junuidin, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
For the past few years, demand for health and beauty products has been high, including bird nests, which has led to the thriving of Malaysia’s swiftlet ranching industry. Hence, the macro parameters related to swiftlet housing characteristics and designs owned by swiftlet ranchers in Sabah and Sarawak were identified. The size of the house, placement of the bird entrance, house orientation, flooring, and location were observed. The descriptive data were analyzed by using ANOVA (p<0.05) and the interaction between variables was determined by using Chi-square regression via SPSS 25.0. The number of swiftlet houses in Sabah was identified as higher than in Sarawak. 57% of the swiftlet houses are in the agricultural area, and 41% of the swiftlet houses are in the forest area. 37% of the chosen orientation by a rancher in Sabah was in the directions of east to west and north to south. This data was significantly different compared to Sarawak as 25% of the houses in Sarawak were constructed from southeast to northwest by the ranchers. The two-floor design was most preferred by the ranchers in Sabah and Sarawak with a total of 43% respectively, followed by a three-floor design at 27% in Sabah and 34% in Sarawak. The size of the swiftlet buildings preferred by ranchers in Sabah and Sarawak was small, with a length and width below 10 feet. Meanwhile, there is no significant difference (p>0.05) in terms of bird entrance, placement, and measurement of the swiftlet houses. Several improvements are needed to reduce the limitation, such as widening the distribution of survey locations or in quantitative aspects, such as edible bird nest production among farmers.